2019
DOI: 10.2147/mder.s205357
|View full text |Cite
|
Sign up to set email alerts
|

<p>Monitoring of postural sway with a head-mounted wearable device: effects of gender, participant state, and concussion</p>

Abstract: Objective: To assess the utility of a head-mounted wearable inertial motion unit (IMU)-based sensor and 3 proposed measures of postural sway to detect outliers in athletic populations at risk of balance impairments. Methods: Descriptive statistics are used to define a normative reference range of postural sway (eyes open and eyes closed) in a cross-sectional sample of 347 college students using a wireless head-mounted IMU-based sensor. Three measures of postural sway were der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 37 publications
(30 reference statements)
2
23
0
Order By: Relevance
“…35 Session-to-session variability and changes due to routine physical activity and potential confounding variables remain well within the 95% CIs for all three sway measures. 35 We have also shown that the device enables on-field detection of abnormal sway to support concussion diagnoses and remove-from-activity/return-to-activity decisions for athletes at risk of impact-induced balance impairments, even in the absence of individual baseline measurements. 35 In the case of concussions and subconcussive head impact exposure, head-mounted devices can also provide the dual functions of continuously monitoring the intensity and frequency of head impacts during athletic activity 36 and quantifying resulting changes in postural stability and balance performance.…”
Section: Introductionmentioning
confidence: 57%
See 4 more Smart Citations
“…35 Session-to-session variability and changes due to routine physical activity and potential confounding variables remain well within the 95% CIs for all three sway measures. 35 We have also shown that the device enables on-field detection of abnormal sway to support concussion diagnoses and remove-from-activity/return-to-activity decisions for athletes at risk of impact-induced balance impairments, even in the absence of individual baseline measurements. 35 In the case of concussions and subconcussive head impact exposure, head-mounted devices can also provide the dual functions of continuously monitoring the intensity and frequency of head impacts during athletic activity 36 and quantifying resulting changes in postural stability and balance performance.…”
Section: Introductionmentioning
confidence: 57%
“…35 We have also shown that the device enables on-field detection of abnormal sway to support concussion diagnoses and remove-from-activity/return-to-activity decisions for athletes at risk of impact-induced balance impairments, even in the absence of individual baseline measurements. 35 In the case of concussions and subconcussive head impact exposure, head-mounted devices can also provide the dual functions of continuously monitoring the intensity and frequency of head impacts during athletic activity 36 and quantifying resulting changes in postural stability and balance performance. 35 The aims of the present study are to investigate applications of the above device as a phybrata sensor, expand our previous investigations to include larger cohorts of clinical concussion patients, and investigate the utility of the device for diagnosing concussions and classifying neurological versus vestibular impairments in patients with diagnosed concussions.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations